Análise de um sistema de produção e seu impacto em indicadores operacionais de uma empresa petroquímica - Aragão, Irlam Reis de (2009)
This work shows in what way an improvement program implemented at Braskem resulted in world class petrochemical processes. The measurement was done in one industrial plant of this company focused on operational efficiency promoted by Six Sigma and TPM methodologies that integrates a program called Braskem+. Three variables were set (physical losses, energy efficiency and overall equipment efficiency) and measured before (2002-2004) and after (2005-2007) Braskem+ implementation. These data were manipulated by using Minitab version 15. The differences between these two sets of data were tested statistically, showing that physical losses and energy efficiency became very close to world class performance. Overall Equipment efficiency by its turn improved significantly but still keeping distance from the better performances in this industry. Additionally it was tested if there was any relationship between efforts applied to implement the program and their results. The efforts variables have been set as hours dedicated and the amount of improvements projects implemented. The results showed that it´s possible to verify a strong correlation between the results obtained thru Six Sigma into physical losses and energy efficiency variables and the efforts measured by hours and projects implemented. In case of TPM and overall equipment efficiency it is possible to verify some king of relationship but it was not possible to confirm if it is strong correlation. This work contributes to analyze the impacts of a important corporate program and records a successful implementation in continuous processes of methodologies normally implemented in discreet processes.